Culturally adapted flowcharts in obstetric emergencies: a participatory action research study - Estefanía Bautista-Valarezo; María Elena Espinosa; Nele R. M. Michels; Kristin Hendrickx; Veronique Verhoeven (BMC, 2022)
Abstract Introduction Maternal mortality is a health problem in developing countries and is the result of several factors such as sociodemographic and economic inequalities and difficulties in accessing the health services. In addition, training strategies in obstetric emergencies targeting the non-medical personnel such as traditional midwives are scarce. The focus of this study is to develop learning and communication bridges on the management of obstetric emergencies and on policies of patients' referral to the biomedical health system in rural areas. Methodology A Participant Action Research (PAR) study with a mixed methods approach was set up to elaborate culturally adapted flowcharts. The project lasted approximately 3,5 years, from September 2016 to January 2021. Results The study was conducted with 94 traditional midwives from southern Ecuador and is divided into 4 phases, namely: 1) Exploration: focus groups and interviews were conducted to document the management of obstetric emergencies through the presentation of "clinical case" scenarios in three important topics, namely: pre-eclampsia, shoulder dystocia and postpartum hemorrhage, 2) Planning: a number of reflective sessions were conducted between the researchers and the healers/midwives to elaborate flowcharts. 3) Action: the training was conducted in rooms dedicated to proficiency in the aforementioned topics and using the flowcharts, 4) Evaluation: 90% of the participants reported having used the flowcharts during the first year after the training. The most frequently used flowchart was that of pre-eclampsia for the recognition of warning signs during pregnancy control. Conclusion This study documents common practices of pregnancy and delivery management by traditional midwives. Furthermore, cultural flowcharts were developed for and together with midwives to improve the clinical response to obstetric emergencies. The preliminary evaluation was favorable; the most frequently used flowchart concerned preeclampsia. In this process, establishing a partnership was crucial for successful intercultural collaboration.